Quadratic Diophantines!

Algebra Level 5

{ 3 ( x 2 + y 2 + z 2 ) = 1 x 2 y 2 + y 2 z 2 + z 2 x 2 = x y z ( x + y + z ) 3 \begin{cases} 3( { x }^{ 2 } + { y }^{ 2 } + { z }^{ 2 } ) = 1 \\ { x }^{ 2 }{ y }^{ 2 } + { y }^{ 2 }{ z }^{ 2 } + { z }^{ 2 }{ x }^{ 2 } = xyz{ \left( x + y + z \right) }^{ 3 } \end{cases} .

Find the number of ordered real triples x , y , z x, y, z satisfying the system of equations above?


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Relevant wiki: Lagrange Multipliers

We treat the first equation as a constraint only, By AM-GM 27 x y z ( x + y + z ) 3 ( x + y + z ) 6 \displaystyle 27 xyz(x+y+z)^3 \le (x+y+z)^6 but 3 ( x 2 + y 2 + z 2 ) ( x + y + z ) 2 3(x^2+y^2+z^2)\ge (x+y+z)^2 . Since we are given that 3 ( x 2 + y 2 + z 2 ) = 1 3(x^2+y^2+z^2)=1 we claim ( x + y + z ) 6 1 (x+y+z)^6\le 1 .

So, x y z ( x + y + z ) 3 1 27 \displaystyle xyz(x+y+z)^3\le \frac{1}{27} . Now consider the expression x 2 y 2 + y 2 z 2 + z 2 x 2 x y z ( x + y + z ) 3 27 ( x 2 y 2 + y 2 z 2 + z 2 x 2 ) \displaystyle \frac{x^2 y^2+y^2 z^2+z^2 x^2}{xyz(x+y+z)^3}\ge 27(x^2 y^2+y^2 z^2+z^2 x^2)

We need to minimize this with the constraint 3 ( x 2 + y 2 + z 2 ) = 1 3(x^2+y^2+z^2)=1 . Set x 2 a , y 2 b , z 2 c x^2\equiv a,y^2\equiv b,z^2\equiv c

If we define the lagrangian as L λ ( a , b , c ) = a b + b c + c a + λ ( 3 ( a + b + c ) 1 ) L_\lambda(a,b,c)=ab+bc+ca+\lambda(3(a+b+c)-1)

Solving the partial derivatives gives a = b = c = 1 9 \displaystyle a=b=c=\frac{1}{9} . And by using Hessian matrix we are sure that it's a minimum. The minimum is 1 1

So, x 2 y 2 + y 2 z 2 + z 2 x 2 x y z ( x + y + z ) 3 27 ( x 2 y 2 + y 2 z 2 + z 2 x 2 ) 1 \displaystyle \frac{x^2 y^2+y^2 z^2+z^2 x^2}{xyz(x+y+z)^3}\ge 27(x^2 y^2+y^2 z^2+z^2 x^2)\ge 1 but here have x 2 y 2 + y 2 z 2 + z 2 x 2 x y z ( x + y + z ) 3 27 ( x 2 y 2 + y 2 z 2 + z 2 x 2 ) = 1 \displaystyle \frac{x^2 y^2+y^2 z^2+z^2 x^2}{xyz(x+y+z)^3}\ge 27(x^2 y^2+y^2 z^2+z^2 x^2)=1 so equality holds and we must have,

x = y = z = ± 1 3 \displaystyle x=y=z=\pm\frac{1}{3} and solutions.

Hey you missed a thing here.how the permutations all can be solutions only the all positive and all negative will do.but the rest 6 are rather cyclic permutations of (-1/√3,0,0) which is 3 and (+1/√3,0,0) which is 3.so total 2+3+3=8

Spandan Senapati - 4 years, 4 months ago

is there another way?

Nitin Kumar - 1 year, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...